Wear Resistance of Ni-Based Alloy Coatings - Jinku Yu; Yuehua Wang; XiCan Zhao; Qinyang Li; Qi Qiao; Jia Zhao; Sen Zhai (Advances in Materials Science and Engineering)
In this paper, nickel-based alloy coatings were deposited on the surface of pure copper by jet electrodeposition. The wear resistance of the coatings was studied by a material surface comprehensive performance tester under dry sliding. Hardness testing, friction, and wear testing were performed to characterize the microhardness, surface morphology, and wear resistance of the coatings. The results indicated that adding Fe and W could refine and purify the microstructure. The coatings with additions of 5 wt.% Fe and 7 wt.% W exhibited the highest wear-resistant properties. Moreover, new compound phases NiO, Fe2O3, and WO3 were found on the surface coatings, such that the microhardness was higher than that in the other coatings. Detailed discussions on the influences of Fe and W on the sliding wear are presented.